Why Choose Volunteering in an Islamic Boarding School? Documenting the Undocumented Voluntary Teaching Motives - EDDY HARYANTO; HARLINA HARJA; DERY MULIA PUTRI; SUPAWAL SUPAWAL; MAD AMIN (Ta'dib: Jurnal Pendidikan Islam, 2018)
This study was part of a larger study aiming at understanding what motives possessed by voluntary teachers of English to teach at one pesantren (Islamic boarding school) in Jambi, Indonesia. The research design of this study was qualitative with a case study approach. The data were collected through demographic profiles and semi-structured interviews with seven female voluntary teachers as the participants of the study to obtain in-depth information regarding implicit and explicit motives to teaching. We analyzed the demographic data descriptively and analyzed the semi-interviews data by using within-case and cross-case displays and analyses. The interview data were digitally recorded, transcribed verbatim, and carefully analysed. The findings indicated that seven voluntary teachers of English implicit and explicit motives to teach English were motivated by interpersonal, community service, the continuation, and non-salary motives.